Female voices: The correspondence of Margaret Plahte, a look at Mexico and the Mexican Revolution (1910-1920) - Arauz Mercado, Diana (Arenal. Revista de historia de las mujeres, 2015)
The participation of national and foreign women about the events during the Mexican Revolution, is mostly known through photographic documents and some others of hemero- graphical character. In that sense, collections of letters written by women are an invaluable treasure when restudying the period mentioned, much more, being the private correspondence maintained by females belonging to diplomatic circles, little insight addressed by historians today. In summary, boldness and feather of the British Margareth Plahte help us look with new eyes who in ten long and difficult years, tried to reorganize a new country.